Towards a gendered STEAM education approach: building a comprehensive model to strengthen girls' and students with non-conforming gender identities' STEAM trajectories in Chilean public schools (UCL Press, 2024)
There is worldwide recognition of the gender gap in STEAM careers. Throughout the world, women are under-represented in STEAM jobs. The explanation for this lies much earlier in girls' educational trajectories. The characteristics traditionally attributed to the feminine and the masculine are reproduced through the preservation of stereotypes in textbooks and teaching practices, which question the meaning of education for girls and students with non-conforming gender identities. By theoretically assuming gender not as a binary but as a mobile category that includes non-conforming gender identities, we sought in this study to construct a comprehensive model to strengthen the trajectories in STEAM areas of girls and those with non-conforming and socially marginalised gender identities in public schools in a semi-rural zone in Chile. We introduce the theoretical foundations of the model and its relevant dimensions and key indicators of development. As a result, this model (in construction) considers the following dimensions: a strategy of collective awareness-raising for the local communities; teacher education in STEAM education; implementation and use of FabLabs and a community centre; and an institutional strategy of accompaniment for schools and students. These are addressed in four moments of participatory research: diagnosis, design, implementation and validation. We discuss the challenges of developing a culturally responsive STEAM education by building a comprehensive model of the above-mentioned groups using a gendered approach that places the binary reproduction of the sex/gender system in tension with the principles of participation and democracy.